Navigational Style Influences Eye Movement Pattern during Exploration and Learning of an Environmental Map - Piccardi, Laura; De Luca, Maria; Nori, Raffaella; Palermo, Liana; Iachini, Fabiana; Guariglia, Cecilia (Frontiers in Behavioral Neuroscience, 2016)
During navigation people may adopt three different spatial styles (i.e., Landmark, Route, and Survey). Landmark style (LS) people are able to recall familiar landmarks but cannot combine them with directional information; Route style (RS) people connect landmarks to each other using egocentric information about direction; Survey style (SS) people use a map-like representation of the environment. SS individuals generally navigate better than LS and RS people. Fifty-one college students (20 LS; 17 RS and 14 SS) took part in the experiment. The spatial cognitive style was assessed by means of the Spatial Cognitive Style Test; participants then had to learn a schematic map of a city, and after five minutes had to recall the path depicted on it. During the learning and delayed recall phases, eye-movements were recorded. Our intent was to investigate whether there is a peculiar way to explore an environmental map related to the individual’s spatial style. Results support the presence of differences in the strategy used by the three spatial styles for learning the path and its delayed recall. Specifically, LS individuals produced a greater number of fixations of short duration, while the opposite eye movement pattern characterized SS individuals. Moreover, SS individuals showed a more spread and comprehensive explorative pattern of the map, while LS individuals focused their exploration on the path and related targets. RS individuals showed a pattern of exploration at a level of proficiency between LS and SS individuals. We discuss the clinical and anatomical implications of our data.